PENGARUH PELATIHAN DAN SISTEM INFORMASI AKUNTANSI TERHADAP KINERJA BENDAHARA - Harlina Nasbin; Nasruil Nasrul; Asrip Putera (Jurnal Manajemen, Bisnis dan Organisasi (JUMBO), 2018)
This study aims to find out and examine: (1) Effect of accounting information systems and training on the performance of the expenditure treasurer of North Konawe District (2) Effect of training on the performance of the expenditure treasurer of North Konawe, (3) Effect of accounting information systems on performance expenditure treasurer of Nort Konawe. This study used a sample of 76 respondents. The analysis tool used is multiple linear regression using the SPSS ver, 23.0 program packageThe results of the study show that: (1) Training and accounting information systems have a significant effect on the performance of the expenditure treasurer of North Konawe, (2) Training has a significant effect on the performance of the spending treasurer of Nort Konawe, (3) The accounting information system has a significant effect on the performance of the spending treasurer of the Nort Konawe.Keywords: training, accounting information system, expenditure treasurer performance